The Effect of Corporate Social Responsibility Compatibility and Authenticity on Brand Trust and Corporate Sustainability Management: For Korean Cosmetics Companies - Lee, Su-Hee; Jeong, Gap-Yeon (Frontiers in Psychology, 2022)
The purpose of this study is to examine whether corporate social responsibility (CSR) activities perceived by consumers affect brand trust and corporate sustainability management (CSM). In other words, this study tried to examine whether the compatibility and authenticity of CSR influences brand trust, thereby affecting CSM including economic viability, environmental soundness, and social responsibility. To measure this, an empirical analysis was conducted on 479 consumers who had experience purchasing products from cosmetic companies that are carrying out CSR. As a result of the analysis, it was found that the compatibility and authenticity of CSR have a positive effect on brand trust. Also, it was found that brand trust had a positive effect on social responsibility among the sub-concepts of CSM, but did not affect economic viability and environmental soundness. The results of this study are expected to provide strategic implications for social responsibility performance and brand trust building necessary for cosmetics companies to grow continuously.